THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND INNOVATION ORIENTATION BEHAVIOR ON EMPLOYEE PERFORMANCE WITH WORK ATTITUDE AS AN INTERVENING VARIABLE (Case study of Islamic Banking Employees) - Adimas Wicaksono; Okder Pendrian (Jurnal Scientia, 2023)
This research aims to determine the influence of emotional intelligence and innovation orientation behavior on employee performance with work attitude as an intervening variable. The population of this study are employees who have worked in sharia banking for less than 1 year to more than 10 years. With a research sample of 100 people. This study uses a quantitative approach. The data in this research uses primary data. Primary data in this research was collected by distributing questionnaires directly and distributing questionnaires using a Google Form link to the research target parties, namely sharia banking employees. The data analysis method in this research uses the Structural Equation Model from the AMOS statistical software package in modeling and hypothesis assessment. The research results show that: (1) emotional intelligence has a positive and significant impact on employee performance. (2) Emotional Intelligence has a positive and significant impact on Work Attitudes. (3) Innovation Orientation Behavior has a positive and significant impact on Employee Performance. (4) Innovation Orientation Behavior has a positive and significant impact on employee Work Attitudes in Sharia Banking. (5) Work Attitude has a positive and significant impact on Employee Performance in the Sharia Banking environment. (6) Emotional Intelligence has a positive and significant indirect influence on Employee Performance through Work Attitudes in the Sharia Banking environment. These findings indicate that the mediation of work attitudes strengthens the relationship between good emotional intelligence and employee performance. (7) Innovation Orientation Behavior has a positive and significant indirect influence on Employee Performance through Work Attitudes in the Sharia Banking environment. These findings indicate that there is mediation between work attitudes and the relationship between good innovation orientation behavior and employee performance.